2008
DOI: 10.1542/peds.2007-2252
|View full text |Cite
|
Sign up to set email alerts
|

Do Cortisol Concentrations Predict Short-Term Outcomes in Extremely Low Birth Weight Infants?

Abstract: OBJECTIVE Relative adrenal insufficiency in extremely low birth weight infants may contribute to significant morbidity and death. Our objective was to evaluate the relationship between cortisol concentrations and short-term outcomes. METHODS Cortisol concentrations were obtained for 350 intubated, extremely low birth weight infants at postnatal age of 12 to 48 hours and at day 5 to 7, as part of a multicenter, randomized trial of hydrocortisone treatment for prophylaxis of relative adrenal insufficiency. Dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
45
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 30 publications
6
45
0
1
Order By: Relevance
“…Identifying infants with relative adrenal insufficiency is difficult; measuring cortisol levels may be useful, however, studies have shown that low cortisol levels are not helpful in defining a population who would benefit from HC therapy. 10,15,16 In our case, information regarding cortisol levels before treatment was not available. Interestingly, those infants who were not pretreated with prophylactic stress HC but subsequently required HC for pressor-resistant hypotension were not clinically different from others in the non-treated group, indicating the challenge of identifying these infants prospectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Identifying infants with relative adrenal insufficiency is difficult; measuring cortisol levels may be useful, however, studies have shown that low cortisol levels are not helpful in defining a population who would benefit from HC therapy. 10,15,16 In our case, information regarding cortisol levels before treatment was not available. Interestingly, those infants who were not pretreated with prophylactic stress HC but subsequently required HC for pressor-resistant hypotension were not clinically different from others in the non-treated group, indicating the challenge of identifying these infants prospectively.…”
Section: Discussionmentioning
confidence: 88%
“…A subset of infants may have an inadequate cortisol response during acute illness that results in changes in vasomotor tone, hypotension and increased dependence on vasopressor support. 13,15 We postulate that relative adrenal insufficiency may have a role in the postoperative decompensation of some premature infants and, providing HC before the stressful event may aid the infants in producing an appropriate response and possibly prevent poor long-term outcomes. Identifying infants with relative adrenal insufficiency is difficult; measuring cortisol levels may be useful, however, studies have shown that low cortisol levels are not helpful in defining a population who would benefit from HC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Despite this, prophylactic supplementation with hydrocortisone in high-risk infants did not reduce the incidence of bronchopulmonary dysplasia. 15 Low cortisol concentrations at day 7 of life, rather than day 1, have been associated with low blood pressure and the need for vasopressor agents, 8 although this was not shown by others, 7 and prophylactic treatment with hydrocortisone did not impact the need for vasopressor therapy. 15 The clinical implication of a low cortisol value, at either day 1 or day 7 of life, remains unclear.…”
mentioning
confidence: 96%
“…This is consistent with other studies that have not found an association between early cortisol concentrations and blood pressure or the need for inotropic support. 7,8 The interpretation of cortisol values in VLBW infants has remained a challenge. In utero, cortisol concentrations are very low and can remain low in healthy preterm infants without demonstrating evidence of relative adrenal insufficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation